By any other name: Accounting for failure in the naming of subject categories - Brown, Mary E (Library & Information Science Research, 1995)
Research shows 65-80% of subject search terms fail to match the appropriate subject heading and one-third to one-half of subject searches result in no references being retrieved. In a cross-sectional study, 82 students (3rd grade through college) were presented complex concepts in a naming task. Concreteness, complexity, and syndeticity contributed significantly in explaining match-failure and predicting match-success. The likelihood of match-success following an initial failure is improved by manipulating the values of these three properties. Developmental trends which worked against match-success were observed. It is suggested that match-failure is a consequence of developmental naming patterns and that these patterns can be overcome through the use of metacognitive naming skills.
Keywords: dept.ils

Book Review: Electronic publishing and libraries. Planning for the impact and growth to 2003 - Brown,DJ - Brown, Mary E (Journal of the American Society for Information Science, 1997)
Keywords: book.review; dept.ils